PENGARUH KURS, HARGA CPO (CRUDE PALM OIL) DAN PROFITABILITAS TERHADAP RISIKO SISTEMATIS DAN IMPLIKASINYA TERHADAP HARGA SAHAM - -, Sunaryo; Kurniawan, Denny (Kinerja, 2020)
The purpose of this research was to determine the influence of Exchange Rate, CPO Price, Profitability on the systematic risk and its implications on stock price. This research sample is the oil palm sub-sector shares listed on the Indonesia Stock Exchange (IDX) period 2007-2016 by using purposive sampling method. There were 6 stocks selected as samples. The analytical method used is Path Analysis, the development of panel data regression with common effects. The results of the study showed found partially that the Exchange Rate, CPO Prices and Profitability has a significant and negative influence on the Systematic Risk. Exchange rates, CPO prices and Profitability partially has a significant positive effect on stock prices. Systematic Risk has a significant negative effect on Stock Prices. The path analysis results show that Systematic Risk mediates the effect of Exchange Rate and Profitability on Stock Prices. However, Systematic Risk does not mediate the effect of CPO Prices on Stock Prices.